The study of quality attributes of parboiled rice during steaming process with revolved sieve - Thatchapol Chungcharoen; Naruebodee Srisang; Siriwan Srisang (My University, 2018)
The steaming process with revolved sieve was studied as a function of steaming time and revolution velocity. The quality of parboiled rice in terms of thermal property, head rice yield and color was investigated and compared to the conventional steaming process such as fixed sieve. The experimental results showed that the steaming process with revolved sieve had advantage over the steaming process with fixed sieve. It led to a steamed sample with higher DG higher head rice yield and lower whiteness value. The required steaming time for a regularity quality by a steaming process with revolved sieve was also shorter. Moreover, the steaming time affected the qualities of parboiled rice. The long steaming time provided the higher DG and head rice yield and lower whiteness value of parboiled rice. Considering revolution velocity, it was found that the revolution velocity did not affect the qualities of parboiled rice. However, the revolution velocity of 5 rpm with steaming time of 5 min provided the difference of quality at each layer.
Keywords: Steaming; Sieve (category theory); Food composition and properties